THE GORONTALO RELIGIOUS COURT JUDGES RESPONSE TOWARD THEIR ABSOLUTE COMPETENCE IN RESOLVING SHARIAH ECONOMY DISPUTES - Mardiana, Andi; Darwis, Rizal (Al-Ulum, 2015)
Post the first amendment of Religious Courts Bill that provides wider authority toward Religious Courts in investigate and decide Islamic economics disputes has responses, whether support or pessimistic, especially among Religious Court judges themselves. This paper examines the Gorontalo Religious Courts judges response about their authority in resolve Shariah economy disputes. This paper is a qualitative descriptive research and the data was collected using observation, interviews and document reviews. The finding of this study revealed that the Gorontalo Religious Courts judges response well to trust laws in handling disputes Shariah economy. In other words, in principle, they are ready to handle disputes Islamic economics. Readiness, such as: the handling disputes Shariah economy is Religious Courts judges authorities and it is a professional responsibility as a judge; Religious Courts formed a special judge to handle falling out or cases of Shariah economy, and Religious Courts judges provides knowledge of Shariah economy without trainings or workshops.Â -----Pasca amandemen pertama undang-undang Peradilan Agama yang memberikan perluasan kewenangan penyelesaian sengketa ekonomi syariâah telah memberikan berbagai tanggapan dari berbagai kalangan, khususnya hakim-hakim Pengadilan Agama. Tulisan ini mengkaji respon para hakim di Pengadilan Agama Gorontalo terhadap kewenangan tersebut. Penelitian ini adalah deskriptif kualitatif dengan metode pengumpulan data melalui observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa hakim Pengadilan Agama Gorontalo merespon baik terhadap amanah undang-undang dalam menangani sengketa perekonomian syariâah. Dengan kata lain pada prinsipnya mereka telah siap menangani sengketa ekonomi syariah. Kesiapan itu antara lain: penanganan sengketa ekonomi syariah adalah sebuah tanggung jawab profesi sebagai hakim; Pengadilan Agama membentuk majelis hakim khusus menangani sengketa atau perkara ekonomi syariâah, dan hakim-hakim Pengadilan Agama dibekali dengan pengetahuan tentang perekonomian syariâah melalui pelatihan-pelatihan.